2015
DOI: 10.1016/j.ijhydene.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A review of solar methane reforming systems

Abstract: Because of the increasing demand for energy and the associated rise in greenhouse gas emissions, there is much interest in the use of renewable sources such as solar energy in electricity and fuels generation. One problem with solar energy, however, is that it is difficult to economically convert the radiation into usable energy at the desired locations and times, both daily and seasonally. One method to overcome this space-time intermittency is through the production of chemical fuels. In particular, solar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(41 citation statements)
references
References 95 publications
(215 reference statements)
0
36
0
1
Order By: Relevance
“…Since methane conversion is thermodynamically favored at elevated temperatures, current industrial practices supply the required process heat through the combustion of a significant portion of the methane feedstock. Owing to the prominence of GTL technologies in industrial fuel production, the development of more sustainable approaches towards syngas production has motivated several research endeavors . Buck et al., as a part of the CAESAR project, demonstrated that concentrated solar energy could replace hydrocarbon combustion as the process heat for the DRM on a 150 kW commercial scale .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since methane conversion is thermodynamically favored at elevated temperatures, current industrial practices supply the required process heat through the combustion of a significant portion of the methane feedstock. Owing to the prominence of GTL technologies in industrial fuel production, the development of more sustainable approaches towards syngas production has motivated several research endeavors . Buck et al., as a part of the CAESAR project, demonstrated that concentrated solar energy could replace hydrocarbon combustion as the process heat for the DRM on a 150 kW commercial scale .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the prominence of GTL technologies in industrial fuel production,t he developmento fm ore sustainable approaches towards syngasp roduction has motivated several research endeavors. [18] Buck et al,a saparto ft he CAESARp roject, demonstrated that concentrated solar energy could replace hydrocarbonc ombustion as the process heat for the DRM on a1 50 kW commercial scale. [19] Through the incorporation of ar hodium catalyst, the reformer achieved methane conversion percentages as high as 69.5 %.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11A shows that the interaction effects of P CH 4 and P H 2 O g ð Þ positively influence the H 2 yield in the linear and quadratic terms. However, it can be inferred that the H 2 production from the interaction of reaction temperature and P H 2 O g ð Þ is mainly by water splitting as reported by Sheu et al 54 Moreover, H 2 yield was also significantly affected by the linear interaction between the reaction temperature and P CH 4 as shown in Figure 11B.…”
Section: Interaction Effects Of Parameters On H 2 Yieldmentioning
confidence: 61%
“…Noble metals are more stable against carbon deposition and also sinter at much higher temperature. On the other hand, noble metals cost more than transition metals (Sheu et al, 2015): for example, 1484 USD/troy Table 1 Comparison between the LM2500 STIG and the hybrid power plant performances (Bianchini et al, 2013 ounce for Pt versus 0.75 USD/troy ounce for Ni. Due to the peculiar MSR reactor working conditions of the hybrid plant described in the paper, which combines low process temperature and high steam-to-methane ratio, the use of Ni based catalyst is favored, thus allowing cost limitation.…”
Section: Solar Thermochemical Receiver/reactormentioning
confidence: 99%
“…A newly integrated receiver/reactor needs to be developed for the application described in the paper. In fact, solar MSR systems developed up to now foresee solar tower as CSP plant (Bianchini et al, 2013;Sheu et al, 2015), while the hybrid power plant described in the paper considers a parabolic trough as CSP plant. Moreover, the aim is to fully integrate receiver and reactor.…”
Section: Solar Thermochemical Receiver/reactormentioning
confidence: 99%